Alveolar Soft Part Sarcoma of Urinary Bladder Occurring as a Second Primary Malignancy: A Case Report and Literature Review - Manint Usawachintachit; Piyada Sitthideatphaiboon; Voranuch Thanakit; Sulada Pukiat; Kamol Panumatrassamee; Julin Opanuraks; Apirak Santi-Ngamkun (Case Reports in Urology)
We report a case of bladder alveolar soft part sarcoma in an 18-year-old Thai male patient who had been treated with testicular radiation and systemic chemotherapy for acute lymphoblastic leukemia with testicular relapse. He presented with recurrent dysuria and gross hematuria. Cystoscopy revealed a 2-centimeter irregular sessile mass at the bladder base adjacent to left ureteral orifice. Transurethral resection of the tumor was performed. The histopathological diagnosis was alveolar soft part sarcoma. Chest and abdominal computed tomography showed no evidence of metastasis. He was treated with partial cystectomy and left ureteral reimplantation with negative surgical margin. No evidence of recurrence was found during a 28-month follow-up period with surveillance cystoscopy and computed tomography of the chest and abdomen.